Still learning: an examination of Quaker stillness as an active teaching method - Simms, Z (2016)
The Religious Society of Friends, known as Quakers, administers nine schools within the UK and these generally operate on Quaker beliefs and principles. There are Quaker schools across the globe; however, just as the disciplines within Quakerism vary around the world so too do their schools. This research is conducted at one UK independent Quaker school and is led by their unique ‘way’ (Advices and Queries 2) of Quakerism. To maintain the anonymity of the school it will be called Fergow School for the purposes of this study. The first observation people often recall when thinking about Quakers is that ‘they sit still in silence’ and indeed this is one identifying marker of the Quaker faith and also of a Quaker school. However, the understanding of what happens in that stillness and silence, especially in a school setting, is undecided. This research aims to show that while you are being still, you can be still learning. Collective worship is a compulsory part of the school day in a ‘Quaker’ faith school setting, but is this time being well spent for and in learning? In a Quaker school, where the vast majority of pupils are not Quakers, this research sought to ascertain whether the stillness and silence of a Quaker Meeting for Worship could be utilised as a space to promote mindfulness, which consequently might enhance the participant’s approach to curriculum learning. This action research discerned whether the school could make better use of current Meeting for Worship time; and also ascertained whether it should implement the practice of mindfulness into the school day. Intervention took the form of exposure to mindfulness teaching to establish whether this made a difference to the student experience of Meeting for Worship. Questionnaires were taken from the intervention group and a control group before and after the intervention sessions took place. Regarding collective worship the focus of the research pertains to the role of collective worship and Meeting for Worship in schools and how Quaker stillness and silence are observed in a Quaker school. Concerning the practice of mindfulness the research considers the type of stillness and silence that are involved in mindfulness and whether this is synonymous with the Quaker form of stillness and silence. In response to these points the main research question is framed: does mindfulness promote learning and is there a way to combine Meeting for Worship with mindfulness in a Quaker school setting. The findings indicated that when exposed to the teaching of mindfulness and mindfulness practice pupils responded more positively to their time spent in Quaker school Meeting for Worship. This meant that collective worship took on greater significance for them and had a greater impact on their school day and home lives. This research therefore demonstrates that collective worship in a Quaker school would be enhanced for the participants it they were taught mindfulness at school. They can then choose to utilise this practice while in Meeting for Worship and as a consequence this can benefit both their well-being and exposure to learning. This innovative method of combining these two educational areas has ramifications for schools who may be considering the use of the time and space spent in collective worship or that are attempting to further the provision of well-being in school by introducing the practice of mindfulness.